Pengaruh Strategi Segmenting, Targeting Dan Positioning Terhadap Keputusan Pembelian Pada Produk Respiro Di Madiun - Meyliana Mega Putri Nareswari; Hartirini Warnaningtyas; Muhammad Imron (Universitas Merdeka Madiun, 2022)
This research aims to test the Effect of Strategy of Segmenting, Targeting and Positioning on the Purchase Decision of Respiro in the City of Madiun. The population in this research are consumers of Respiro products in Madiun. The data used is primary data obtained from distributing questionnaires through Google Form. The amount of data obtained is 100 respondents. The data obtained were tested with validity test, reliability test, multiple linear regression analysis test, and classical assumption test using SPSS version 18.00. The results of this research indicate that the segmenting variable has a partial influence on purchasing decisions on Respiro products in Madiun, the targeting variable has no partial influence on purchasing decisions for respiro products in Madiun, positioning has a partial influence on purchasing decisions for respiro products in Madiun and Segmenting, Targeting and Positioning simultaneously affect the Purchase Decision on Respiro Products in Madiun.